Konstruksi Keilmuan Fikih Nusantara: Perspektif Filsafat Sains - Bashori, Akmal (DIKTUM: Jurnal Syariah dan Hukum, 2022)
Nusantara jurisprudence is the embodiment of jurisprudence in the nusantara, jurisprudence is constructed in accordance with the culture of the people, so that there is a dialectical process between culture and naṣ. The question is, does the fiqh that is practiced have to be the same as the fiqh where Islam itself descends, or can fiqh be dialectic with locality so that it gives rise to fiqh with the characteristics of each regional locality? How is the scientific construction of the fiqh nusantara from the perspective of the philosophy of science? Thus, this paper aims to find out how the scientific construction of the archipelago's fiqh from the perspective of the philosophy of science. With a philosophical approach, this paper will describe how the scientific construction of the fiqh nusantara. From this paper it is found that: first, in the perspective of philosophy of science, the material object of the fiqh nusantara is fiqh mu’āmalāh which contains several aspects: mu’āmalāh / property, jinayat, aḥwāl syakhsiyah, zakāt and waqf, qada, and nationality; second, the formal object of the archipelago's fiqh is divided into ontology, which contains the concept of al-tsabit, and mutagoyyirat, epistemology which contains the theory of knowledge of the archipelago's fiqh, among others: Authoritative Sources (al-Qur’an & Sunah), Ijtihād (Ijmā, Qiyās, Istiḥsān, Istiṣlāh, 'Urf, Saḍ Dzariah), and axiology, namely maqāṣid sharī'ah in this case to guide humans in capturing God's intentions wisely.